Gliding length at different slope in three cross country skiing techniques - Pellegrini, B.; Zoppirolli, C.; Bortolan, L.; Schena, F. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
A significant part of mechanical work in cross country skiing is spent to overcome friction. The amount of that work is however dependent, other than by friction coefficient and by application of normal forces, by the extent of space traveled by gliding. The aim of this study was to quantify cycle, swing and gliding length for double poling (DP), diagonal stride (DS) and double poling with kick (DK) at different slopes.